The Role Of Teamwork In Improving Patient Safety Culture - Febriansyah Febriansyah; Rokiah Kusumapradja; Hasyim Ahmad (Universitas Muhammadiyah Yogyakarta, 2020)
Since the declaration of patient safety culture in the hospital X in 2015, there were 171 cases of patient safety incident until December 2018, with Near Injury Incidence (KNC) dominated at 56%. Of all the patient safety incidents, about 60% occurred in the treatment facility. Poor coordination among nurses has led to the absence of the same perception on the filling of incident reporting formats, the choice of incidents that had not been so precise, and a feeling of fear of being blamed when reporting an incident. The purpose of this research is to analyze the influence of leadership styles, teamwork, and knowledge of the safety culture of patients at X Hospital, Bekasi. The study aims to analyse the influence of leadership style, teamwork, and knowledge on patient safety culture at X Hospital, Bekasi. This research method uses the analytical causality approach, conducted by a survey method and its correlation technique with the time dimension of one short study. The sample in this study were nurses in the inpatient installation. Sampling size determined using the Purposive Sampling technique resulting in 98 samples. Data analysis uses multiple regression test. The result showed that leadership style, teamwork, and knowledge influence either partially or simultaneously to patient safety culture at X Bekasi Hospital. The dominant of independent variables is teamwork. Finding: In-hospital services, the role of teamwork is significant in creating the patient safety culture. Implications: Hospital management must involve the active role of each team member in improving patient safety culture.